Teaching Sports and Exercises Science: experiences and life skills of a lecturer - Francesco V Ferraro (Firenze University Press, 2023)
The following document reports the experiences and life skills developed under the current didactic situation in Sports and Exercise Science. In particular, the manuscript discusses the pedagogic theories that should be fostered to improve the return to campus. The real-life experiences are presented in light of the Social and Emotional Learning and the Learning by Doing theories. The following document aims to reflect on social constructivism and embodied theories to improve the new (post-covid) learning environment. The introduction focuses on the Quality Assurance Agency for Higher Education benchmark statement and progresses to the most recent Blended approaches. With reflections upon in-class assessments, spaces and pace. In conclusion, the cartesian dualism (body-mind) is discussed and ideas for future research in pedagogy are presented to improve teaching and learning experiences in the post-covid scenario.   Insegnare Scienze Motorie: esperienze e abilità di un docente universitario. Il documento ha come scopo quello di riflettere sul costruttivismo sociale e sulle embodied theories per migliorare il nuovo ambiente di apprendimento (post-covid). Il seguente documento riporta le esperienze e le abilità sviluppate nell'attuale situazione didattica, nello specifico riguardo le scienze motorie. In particolare, nel testo sono discusse le teorie pedagogiche che dovrebbero essere incoraggiate per migliorare il ritorno in aula. Le esperienze didattiche sono presentate alla luce delle teorie dell'apprendimento sociale ed emotivo e del Learning by Doing. L'introduzione si concentra sul Quality Assurance Agency for Higher Education benchmark e presenta i più recenti approcci didattici definiti Blended, con l'aggiunta di riflessioni su valutazioni, spazi e ritmo della classe. In conclusione, viene discusso il dualismo cartesiano (corpo-mente) e vengono presentate idee per future ricerche in pedagogia al fine di migliorare le esperienze di insegnamento e di apprendimento nello scenario post-covid.